Analysis of Pharmacies in South Georgia - Birdine, Destiney; Borzi, Richard A.; Campbell, Drew; Daniel, Cameron; Day, Kaylon A.; Hill, Hannah J.; Singeltary, Ben; Tyson, Luis; Ward, Stewart (My University, 2020)
Pharmacy is an important part of healthcare, and the accessibility to a pharmacy is a concern in Lowndes County. Studies have shown that residents of rural areas and small cities tend to have lower accessibility to pharmacies. However, no such study has been conducted for Lowndes County, which includes most rural areas and small cities. The objective of this project is to involve our students in the analysis of pharmacy locations in Lowndes County. We collected and assembled location data of pharmacies in South Georgia into a digital database and utilized Geographic Information System (GIS) to map all locations. Through map analysis, we conclude that there is a problem for rural and small city residents in Lowndes County to access pharmacies. We suggest our government officials to increase accessibility and improve access to pharmacies in Lowndes County.